Circumferential defect detection using ultrasonic guided waves: An efficient quantitative technique for pipeline inspection. Issue 6 (24th February 2020) - Da, Yihui; Dong, Guirong; Shang, Yan; Wang, Bin; Liu, Dianzi; Qian, Zhenghua
Abstract : Purpose: Quantitatively detecting surface defects in a circular annulus with high levels of accuracy and efficiency has been paid more attention by researchers. The purpose of this study is to investigate the theoretical dispersion equations for circumferential guided waves and then develop an efficient technique for accurate reconstruction of defects in pipes. Design/methodology/approach: The methodology applied to determine defects in pipelines includes four steps. First, the theoretical work is carried out by developing the appropriate dispersion equations for circumferential guided waves in a pipe. In this phase, formulations of strain-displacement relations are derived in a general equidistant surface coordinate. Following that, a semi-analytical finite element method (SAFEM) is applied to solve the dispersion equations. Then, the scattered fields in a circular annulus are calculated using the developed hybrid finite element method and simulation results are in accord with the law of conservation of energy. Finally, the quantitative detection of Fourier transform (QDFT) approach is further enhanced to efficiently reconstruct the defects in the circular annuli, which have been widely used for engineering applications. Findings: Results obtained from four numerical examples of flaw detection problems demonstrate the correctness of the developed QDFT approach in terms of accuracy and efficiency. Reconstruction of circumferential surface defects using the extended QDFT method can be performed without involving the analytical formulations. Therefore, the streamlined process of inspecting surface defects is well established and this leads to the reduced time in practical engineering tests. Originality/value: In this paper, the general dispersion equations for circumferential ultrasonic guided waves have been derived using an equidistant surface coordinate and solved by the SAFEM technique to discover the relationship between wavenumber of a wave and its frequency. To reconstruct defects with high levels of accuracy and efficiency, the QDFT approach has been further enhanced to inspect defects in the annular structure.